REPOSISI DAN EKSISTENSI MADRASAH SALAFIYAH DI ERA GLOBAL - Salahuddin, Marwan (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2013)
Abstract: Madrasah is an educational institutions have developed varied , with the times . Most madrasah became public educational institutions distinctively Muslim ,most complete knowledge of religion taught in public schools because of the number of hours of very few studies , some still remain committed madrasah as an institution thatÂ  studiesÂ  theÂ  IslamicÂ  sciencesÂ  . ThenÂ  this madrasahÂ  is referredÂ  toÂ  the Madrasah Salafiyyah . Generally, these types of madrasah teach Islamic sciences which writes by Ulama Salaf, so if it is associated with the development of science and technology inÂ  this globalization era has missed most ofÂ  the materialÂ  , butÂ  inÂ  factÂ  this kind of madrasah still exist with a variety of activities . This can happen because the madrasah managers capable of adapting to changes in the global era . Old tradition that is still well maintained in order to fortify the negative influence of the various cultures that can undermine Islamic valuesÂ Â  . Similarly, the maintenance of the valuesÂ Â  as the basis for the formation of character with more emphasis on the primacy of worship and devotion to duty as a parent and teacher glorify ukhrawi approach continue to be preserved . Thus madrasah salafiyah will be more in demand , due to appear in the form of a new face, but the valuesÂ Â Â  still follow the previous scholars.Â Ø¶Ø¹Ø¨ ØØ¨ØµØ£Ù ØÙØ§ÙØ²ÙØ§ ÙØ¯ÙØª Ø¨ÙØ§ÙØª Ø§Ø¹ÙÙØªÙÂ  â Ø©ÙÙÙØ³Ø¥ Ø©ÙÙØ¨Ø±Øª Ø©Ø³Ø³Ø¤ÙÙ â Ø©ÙÙÙØ¯ÙØ§ Ø©Ø³Ø±Ø¯ÙØ§ ØªÙ :ØµØ®ÙÙÂ Ø©ÙØ¨ÙØ±Ø¬ØªÙØ§ ÙÙÙØ¹ÙØ§Ø¨ Ø©ÙÙÙØ¯ÙØ§ Ø¯Ø§ÙÙØ§ ØªÙÙÙØ£ Ø±Ø®ÙØ§ Ø¶Ø¹Ø¨ÙØ§Ù ØØ©ÙÙÙØ³Ø¥ Ø©Ø²ÙØ¨ Ø©Ø²ÙÙØªÙØ§ Ø©ÙØ§Ø¹ Ø©ÙÙØ¨Ø±Øª Ø©Ø³Ø³Ø¤Ù Ø³Ø±Ø§Ø¯ÙØ§Â ÙÙ Ø«ÙØ§Ø«ÙØ§ Ø¹ÙÙÙØ§Ù .Ø·ÙÙ Ø©ÙÙÙØ³ÙØ§ ÙÙÙØ¹ÙØ§ Ø³Ø±Ø¯Øª ÙØ§Ø²Øª Ù ØªÙØ§ Ø©Ø³Ø±Ø¯ÙØ§ Ø±Ø®ÙØ§ Ø¶Ø¹Ø¨ÙØ§Ù ØØ©ÙÙÙÙ Ø§ÙØªØµØ Ø¯Ø¯Ø¹ ÙÙÂ Ø¡Ø§ÙÙØ¹ÙØ§ ÙÙÙØ£Øª Ø©ÙÙÙØ³ÙØ§ Ø¨ØªÙÙØ§ Ø³Ø±Ø¯Øª â Ø©ÙØ§Ø¹ â Ø©Ø³Ø±Ø¯ÙØ§ ÙØ°Ù ÙØ«Ù ÙØ¥ . Ø©ÙÙÙØ³ÙØ§ Ø©Ø³Ø±Ø¯ÙØ§Ø¨ ÙÙØ³ÙØ§ ÙÙ Ø©Ø³Ø±Ø¯ÙØ§Â Ø©ÙØ¦Ø§ÙÂ  Ø³Ø±Ø§Ø¯ÙØ§Â  ÙØ°Ù ÙÙÙÂ  ØØ©Ø±Ø®Ø£ØªÙ Ø§ÙØ¯Ø§ÙÙ Ø¶Ø¹Ø¨Â  ÙØ§Ù ØØ§ÙØ¬ÙÙÙÙÙØªÙØ§Ù ÙÙÙØ¹ÙØ§Â  ÙØ¯ÙØªØ¨Â  ÙØ±ÙÙÂ  ÙÙÂ  ÙØªØ ØÙÙÙØ§Ø³ÙØ§Â ÙÙØ¹ Ø©Ø³Ø±Ø¯ÙØ§ ØªØ¸ÙØ§ØÙ ØØ©ÙÙØ¹ÙØ§ Ø±ØµØ¹ Ù ØªØ§ÙØºØªÙØ§ Ø¹Ø§ÙÙØ£Ø¨ Ø©Ø³Ø±Ø¯ÙØ§ Ø¬ÙØ¯ ÙÙØ¹ Ø±Ø¯Ø§Ù Ø©Ø³Ø±Ø¯ÙØ§ ÙØ°Ù ÙØ¸ÙÙ ÙÙ ØØ©ØªØ¨Ø§Ø«Â ÙÙÙØ³ÙØ§ ÙÙÙÙØªÙ ÙÙÙÙØ§ ÙÙØ¹ ÙÙØ°Ù Ø¸ÙØ§ØªÙ .Ø©ÙØ§Ù Ø¯ÙØ§ ØªØ§Ø±Ù Ø«Ø¤ÙØ§ ÙØ¹ Ø©ÙÙÙØ³ÙØ§ ÙÙÙÙØ§ Ø¸Ø§ÙÙ Ø©ÙØ§ØµÙØ§ Ø©ÙØ¯ÙÙØ§ ÙÙÙÙØ§Â ÙÙÙØªØ³ ØØ§ÙÙÙ ÙØ°ÙØ¨ .ÙÙØ±Ø®ÙØ§ ÙØ®Ø¯ÙØ§Ø¨ ÙÙÙØ¹ÙØ§Ù ÙÙØ¯ÙØ§ÙÙØ§ ÙØ§Ø±ÙØ¥ Ø¨ÙØ¬ÙÙ Ø©ÙØ¯ÙØ¨Ø¹ÙØ§Ù Ø©Ø¯Ø§Ø¨Ø¹ÙØ§ ØÙØ± ÙØ¥ ÙØ§ØªÙØ§Ø¨.ÙØ§ØµÙØ§ ÙÙØ³ÙÙ ÙÙÙÙØ§ ØªØ¹Ø¨ØªØ§ Ø§ÙÙÙÙ Ø¯ÙØ¯Ø¬ ÙØ¬ÙØ¨ ØªØ±ÙØ¸ Ø§ÙÙÙ ØØ¨ÙØ·ÙØ§ ØªØ§Ø¨ØºØ± Ø¹Ø¶ÙÙ Ø©ÙÙÙØ³ÙØ§ Ø³Ø±Ø§Ø¯ÙØ§ ÙØ°Ù